Half-life measurements of 212Po with thorium-loaded liquid scintillator - P. Belli; R. Bernabei; R. S. Boiko; F. A. Danevich; A. Di Marco; A. Incicchitti; D. V. Kasperovych; F. Cappella; V. Caracciolo; V. V. Kobychev; O. G. Polischuk; N. V. Sokur; et al. (Ядерна фізика та енергетика)
Precise measurement of half-life of 212Po (one of the daughter nuclides in radioactive chain of 232Th) was realized by means of liquid scintillator based on toluene doped by complex of thorium and trioctylphosphine oxide with concentration of Th ≈ 0.1 mass %. Fast photomultiplier tube and high frequency oscilloscope were used to acquire the scintillation signals waveforms. The algorithms were developed to find pairs of 212Bi β-decays and subsequent 212Po α-decays, to calculate time differences between the events in the pair, and to build 212Bi β-decay and 212Po α-decay energy spectra. Preliminary the 212Po half-life is T1/2 = (294.8 ± 1.9) ns. The experiment is in progress aiming at reduction of the statistical and systematic uncertainties.